UJI ORGANOLEPTIK DAN SIFAT KIMIA KUE SEMPRONG CAMPURAN TEPUNG UBI JALAR UNGU (IPOMOEA BATATAS) DAN TEPUNG TERIGU - Montolalu, Olfita S.; Langi, Tineke M.; Koapaha, Teltje (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2020)
ABSTRACTThe aim of this research is to produce a quality semprong cookies by mixing purple sweet potato flour and flour properly, based on the panelists' preference level and the nutritional characteristics of the "semprong" cake. The organoleptic test results of the "semprong" cake which are preferred in terms of color, taste, aroma and texture are treatment A (10g purple yam flour + 90g wheat flour). The results of the proximate content analysis of "semprong" cakes for water content ranged from 3.16% - 3.77%, ash content ranged from 1.32% - 2.09%, fat content ranged from 16.26% - 20.95%, content protein ranges from 7.06% - 8.95%, carbohydrate content ranges from 66.31% - 71.21%.Keywords : Semprong Cake, Purple Sweet Potato Flour, Wheat Flour